Assessing the Risk Factors and Pregnancy Outcomes of Toxoplasmosis Infection - Mohamed Errmali; Huda Eldeeb (AlQalam Journal of Medical and Applied Sciences, 2025)
Toxoplasmosis is considered a zoonotic food-borne infection caused by the parasite Toxoplasma gondii. During pregnancy, the Toxoplasma gondii infection is found to contribute to miscarriages, stillbirth, neonatal death, or fetal/neonatal abnormalities via vertical transmission, which increases with gestational age. The current study was conducted to determine the risk factors and pregnancy outcomes of Toxoplasmosis infection among Libyan pregnant women. This study was a case series hospital-based study carried out in the obstetrics and gynecology sectors of Ali Omar Askar Hospital, Alkhadra Hospital, and Alafia Clinic between January 2019 and April 2025. A total of 60 pregnant women who were diagnosed with toxoplasmosis in a multicenter hospital which collected from medical records via a standardized questionnaire. The extracted data underwent analysis and processing via SPSS version 24. A total of 60 pregnant women were included, aged between 30 and 34 years, and accounted for 24(40.0%). The mean age was 29.27±5.210SD. The mean gestational age was 14.52 ± 4.019 SD with the minimum gestational age was 9 weeks while the maximum gestational age was 24 weeks and 58.3% (35) of patients had expressed history of animal contact particularly cat accounted 10.0% (6), 68.3% (41) of patients had received antibiotics therapy with 20.0% (12) had received Spiramycin followed by 18.3% (11) had received Pyrimethamine and 16.7% (10) had received Azithromycin. 28.3% (17) of neonates had expressed jaundice, followed by 25.0% (15) had expressed pneumonitis, 13.3% (8) had expressed skin rash, and 8.3% (5) had expressed hydrocephalus. just 11.7% (7) had expressed chorioretinitis, 10.0% (6) had developed epilepsy, 1.7% (1) had blindness, and 1.7% (1) had strabismus after delivery. statistically significant results were reported on the relationship between neonatal complications and toxoplasmosis outcomes (P-value = 0.041). 46.7% (28) of them had required admission to the neonatal intensive care unit. Several risk factors have been identified linked to toxoplasmosis, such as the middle age group, early gestational age infection exposure, history of animal contact, and early antibiotics therapy. Most patients reported that they received antibiotic therapy, which contributed to a lower rate of fetal and neonatal complications. Therefore, early recognition as well as prompt management of toxoplasmosis is our crucial approach to avoid related adverse perinatal outcomes. Also, effective prenatal counseling and antenatal screening for the high-risk group in toxoplasmosis infection are essential to prevent related perinatal morbidity and mortality.